2020
DOI: 10.14814/phy2.14351
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive sublingual microvascular imaging reveals sex‐specific reduction in glycocalyx barrier properties in patients with coronary artery disease

Abstract: Background: Risk factors for coronary artery disease (CAD) have been associated with endothelial dysfunction and degradation of the endothelial glycocalyx. This study was designed to compare sublingual microvascular perfusion and glycocalyx barrier properties in CAD patients and controls using noninvasive side stream darkfield imaging. Methods: Imaging of the sublingual microvasculature was performed in 52 case subjects (CAD confirmed by left heart catheterization) and 63 controls (low Framingham risk score). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…In chronic diseases, compensatory responses may offset changes in shedding or expression. For example, in one study assessment of the glycocalyx by SDF imaging showed no significant difference in glycocalyx dimensions between patients with and without cardiovascular disease 227 . However, two studies have reported elevations in sdc‐1 and HA in patients with cardiovascular disease 159,184 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In chronic diseases, compensatory responses may offset changes in shedding or expression. For example, in one study assessment of the glycocalyx by SDF imaging showed no significant difference in glycocalyx dimensions between patients with and without cardiovascular disease 227 . However, two studies have reported elevations in sdc‐1 and HA in patients with cardiovascular disease 159,184 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in one study assessment of the glycocalyx by SDF imaging showed no significant difference in glycocalyx dimensions between patients with and without cardiovascular disease. 227 However, two studies have reported elevations in sdc-1 and HA in patients with cardiovascular disease. 159,184 Support for compensatory reaction(s) can be inferred from an in vivo study of the glycocalyx in sdc-1 knock-out (KO) mice where Savery et al used micro-particle velocimetry to determine the presence of a hydrodynamically significant cell surface layer.…”
Section: Discussionmentioning
confidence: 99%
“…In coronary artery disease, both males and females have significantly impaired sublingual microvascular perfusion compared to controls. However, women, but not men, exhibited a significantly larger PBR, indicting a reduction in glycocalyx barrier function suggesting sex dependency 32 …”
Section: Discussionmentioning
confidence: 91%
“…Thus, eGCX thickness inversely correlates with microvascular perfusion of this boundary region [ 100 ]. Increased PBR values were described in patients with CAD and cerebral atherosclerosis, indicating an impaired eGCX during atherosclerosis progression [ 101 , 102 ].…”
Section: The Endothelial Glycocalyx (Egcx) and Its Role In Atherosclementioning
confidence: 99%